2016
DOI: 10.1089/dia.2015.0369
|View full text |Cite
|
Sign up to set email alerts
|

Use of Glucose Rate of Change Arrows to Adjust Insulin Therapy Among Individuals with Type 1 Diabetes Who Use Continuous Glucose Monitoring

Abstract: Objective: This study was performed to understand and to compare differences in utilization of continuous glucose monitoring (CGM) and the rate of change (ROC) arrow to adjust insulin therapy among individuals with type 1 diabetes (T1D), comparing those treated with multiple daily insulin injections (MDI) with those treated with continuous subcutaneous insulin infusion (CSII). Research Design and Methods: We surveyed 222 T1D individuals who regularly used real-time CGM to obtain information about general CGM u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The majority of CGM users in this study also reported using ROC arrows frequently to guide changes in their insulin dosage, with these changes more aggressive than the recommended 10%-20% adjustments commonly advised. 6 …”
Section: Accuracymentioning
confidence: 99%
“…The majority of CGM users in this study also reported using ROC arrows frequently to guide changes in their insulin dosage, with these changes more aggressive than the recommended 10%-20% adjustments commonly advised. 6 …”
Section: Accuracymentioning
confidence: 99%
“…Therefore, there is a clear need to provide a framework to patients and clinicians on how to make these adjustments. 37 …”
Section: Evidence For Efficacy Of Rtcgm Usementioning
confidence: 99%
“…No systematic evaluations have been reported on the information most often used in daily life to guide insulin adjustment decisions, i.e., whether individuals with diabetes mostly rely for decisions on insulin dose adjustment on the current glucose value, the glucose profile over the previous few hours, or the "trend arrow" (which indicates when the blood glucose is rapidly falling or rising but differs in format between devices) (44,45) [3e].…”
Section: Data Handling and Reportingmentioning
confidence: 99%